2020
DOI: 10.1111/desc.12940
|View full text |Cite
|
Sign up to set email alerts
|

Numerosity discrimination in deep neural networks: Initial competence, developmental refinement and experience statistics

Abstract: It is well accepted that both humans and non-human animals are able to make approximate judgments of relative numerosity (Dehaene, 2011). Discriminability of two visual numerosities can be characterized, at least approximately, as a function of their ratio, in accordance with Weber's law (Dehaene, 2003). Notably, ratio-dependent performance has been observed also

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 61 publications
0
49
0
3
Order By: Relevance
“…In our stimulus space Numerosity, Size and Spacing varied within the same range, in order to make sure that one dimension was not statistically more salient (i.e., of higher variance) than the others. However, an interesting research direction could be to investigate how the representational space might change under different distributional properties, for example by creating stimuli that match the statistical distribution of visual features in natural environments 50 . www.nature.com/scientificreports www.nature.com/scientificreports/ Our simulations show that numerosity processing can be carried out using generic low-level computations, such as those emerging in multi-layered neural networks that learn a hierarchical generative model of the sensory data.…”
Section: Discussionmentioning
confidence: 99%
“…In our stimulus space Numerosity, Size and Spacing varied within the same range, in order to make sure that one dimension was not statistically more salient (i.e., of higher variance) than the others. However, an interesting research direction could be to investigate how the representational space might change under different distributional properties, for example by creating stimuli that match the statistical distribution of visual features in natural environments 50 . www.nature.com/scientificreports www.nature.com/scientificreports/ Our simulations show that numerosity processing can be carried out using generic low-level computations, such as those emerging in multi-layered neural networks that learn a hierarchical generative model of the sensory data.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we believe that a deeper understanding of numerosity perception will require considering alternatives to the search for evidence of adherence to idealized, essential characteristics: We should also strive to define what could be the underlying mechanisms giving rise to the complex behavioral patterns observed in these studies. Promising results in this direction have been recently achieved by connectionist modelingfor example, by showing how approximate adherence to Weber's law can emerge in generic neural networks that learn the statistics of their visual environment (Stoianov & Zorzi, 2012;Zorzi & Testolin, 2018), or how developmental trajectories of numerical acuity in children can be simulated by progressive deep learning (Testolin, Zou, & McClelland, 2020). Further research is required to explore these issues more fully, keeping in mind that we must be prudent when characterizing the actual patterns observed in the empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, basic visuospatial processing in a hierarchical structure together with statistical properties of the object may be sufficient for the emergence of numerical competence even in non-trained networks (Zorzi and Testolin, 2018); moreover, progressive experience can refine and improve this representation resembling developmental advances. It has been suggested that a dedicated system for numerosity also in animals might not be necessary since learning mechanisms of the neural system could be sufficient to extract that information from natural environments, as it is in the case of artificial networks (Testolin et al, 2020b).…”
Section: Neural Networkmentioning
confidence: 99%